Utility of global longitudinal strain in early identification of chronic cardiotoxicity in asymptomatic long-term malignant lymphoma survivors with normal left ventricle ejection fraction - Rihackova, Eva; Rihacek, Michal; Boucek, Lubos; Vyskocilova, Maria; Elbl, Lubomir (Scientific reports, 2025)
Malignant lymphoma survivors are at increased risk for anthracycline and/or radiotherapy-induced chronic cardiotoxicity. Proper long-term follow-up is essential for malignant lymphoma survivors after-care. This study aimed to assess TTE parameters of potential subclinical cardiotoxicity and to examine their utility in diagnosing chronic cardiotoxicity. Improvement of the diagnostic process may precede the manifestation of cardiac adverse events. Main objective of the study was to improve the identification of cancer survivors in increased risk of treatment cardiotoxicity. To achieve this goal, utility of various echocardiography parameters was examined.In this retrospective study we analysed TTE of 167 subjects with speckle tracking according to the European Society of Echocardiography guidelines during the follow-up period. 88 of them were long-term lymphoma survivors diagnosed with malignant lymphoma between the years 1994-2015. Minimum follow up period was 5 years with the median of 10 years after anti-cancer treatment cessation. TTE were performed between the years 2017-2022 at cardio-oncology outpatient office during regular follow-up period. A total of 79 volunteers with no history of chronic heart failure (CHF) or decline in LVEF, 51 (64.6%) of whom were males, with the median age of 46 (16-58) years were included in the analysis as control group. Control subjects had various indications for TTE (e.g. preoperative examination, benign palpitations, or with well controlled arterial hypertension taking two antihypertensives at most). Ischemic heart disease was ruled out by stress test. None of the control subjects had history of stroke or chronic lower limb ischemia. All control subjects were considered clinically stable with no sign of cardiac impairment caused by primary disease. Both cancer survivors and control group were divided into subgroups based on LVEF: lower normal LVEF (53-61%), and higher normal LVEF (> 61%). Survivors with lower normal LVEF (53-61%) had a statistically significant decline in GLS compared to those with higher normal LVEF (> 61%). This phenomenon was not observed in control group indicating a possible additional diagnostic value of this parameter. Inclusion of GLS assessment in follow-up TTE examination of subjects with lower normal LVEF may improve the sensitivity of detection of chronic cardiotoxicity. Patients with declined GLS and lower normal LVEF are candidates for intensified follow-up to precede manifestation of cardiac adverse events.
Keywords: funkce levé komory srdeční; následné studie; Cardiotoxicity; lidé; mladiství; Middle Aged; Adult; přežívající onkologičtí pacienti; Lymphoma; Female; antracykliny; retrospektivní studie; Adolescent; Humans; tepový objem; Ventricular Function, Left; lymfom; Follow-Up Studies; Anthracyclines; Stroke Volume; echokardiografie; kardiotoxicita; lidé středního věku; mužské pohlaví; mladý dospělý; Cancer Survivors; globální longitudinální strain; ženské pohlaví; Young Adult; Male; Retrospective Studies; Global Longitudinal Strain; dospělí; Echocardiography